Aspectos legais e ambientais do descarte de resíduos de medicamentos - Rodrigues, Carla Regina Blanski (2009)
The environment risks arising of the inadequate discard of pharmaceutical waste has increased with the technology progress, and also with the advance and the aging of the population. The entry route of this kind of waste in the environment is through the domestic sewer’s launch into the water’s route, effluent of pharmaceutical industry, rural effluents, and improper disposal of pharmacist after the end of the expiry date. Therefore, the waste follows with the gross sewer to the stations of sewage treatment, however the usual processes of treatment which the waste is submitted does not remove the pharmaceutical waste. The purpose of this work was analyzing the legal and environment aspects of the allopathic pharmaceutical waste’s final discard. It is a descriptive and exploratory research, achieved through fieldwork activities, and with the help of companies related with production, distribution, and commerce of pharmaceutical products used by humans, as well as in the literature investigation and in the current legislation. It has been verified that the drugs, even with their characteristic of micro pollutant, it may cause significant impacts to the environment. Brasil has achieved great advances in legislation; however there are some divergences between the regulatory aspects that still remain. About the principle of the payer polluter, this is very complex and it can have a lot of different interpretations. In the pharmaceutical department there are divergences about the responsibility of the discard, because the pharmaceutical laboratories say that the responsibility is of the chemistry industry and they passes to the laboratories. Thus, it has found that the discard of drugs is being done by the drugstores, the weaker part of the distribution process, and therefore, not applying the principle of the payer polluter and also by the final consumer, but in an inadequate way. In this context, the protagonists involved in the pharmaceutical commerce and governmental institutions should organize themselves, so they could offer logistic support of distribution and reverse to this national level action, consequently helping in an effective way to the environmental sustainability.